Liquid crystal formation in supercoiled DNA solutions. - Zakharova, Svetlana S (2002)
The critical concentrations pertaining to the liquid crystal formation of pUC18 plasmid in saline solutions were obtained from (31)P nuclear magnetic resonance, polarized light microscopy, and phase equilibrium experiments. The transition is strongly first order with a broad gap between the isotropic and anisotropic phase. The critical boundaries are strongly and reversibly dependent on temperature and weakly dependent on ionic strength. With polarized light microscopy on magnetically oriented samples, the liquid crystalline phase is assigned cholesteric with a pitch on the order of 4 microm. Preliminary results show that at higher concentrations a true crystal is formed. The isotropic-cholesteric transition is interpreted with lyotropic liquid crystal theory including the effects of charge, orientation entropy, and excluded volume effects. It was found that the molecular free energy associated with the topology of the superhelix is of paramount importance in controlling the width of the phase gap. The theoretical results compare favorably with the critical boundary pertaining to the disappearance of the isotropic phase, but they fail to predict the low concentration at which the anisotropic phase first appears.